Bioaccumulation and exposure to potentially toxic elements (PTEs) in marine species commercialized for human consumption in the Southern Region of Rio de Janeiro (SE, Brazil) - Graziele Arantes Reis; Maria Virginia Alves Martins; Carla Patinha; Pedro Pato Martins; Eduardo Ferreira da Silva; Rubens Cesar Lopes Figueira; Cassio Roberto da Silva; Fernando Rocha (Marine Pollution Bulletin, 2026)

Natural antifungals for managing black spot disease in papaya: Efficacy of essential oils and bioactive compounds against Asperisporium caricae - Adilson Vidal Costa; Maria Laura Urbano Nascimento; Lais Oliveira Rodrigues; Mariana Belizario de Oliveira; Walter Cesar Celeri Bigui; Poliana Aparecida Rodrigues Gazolla; Matheus Ricardo da Rocha; Willian Bucker Morais; Juliana Alves Resende; Gabriel Jacomin Vargas da Silva; Róbson Ricardo Teixeira; Vagner Tebaldi Queiróz; et al. (Postharvest Biology and Technology, 2026)

Oral supplementation with Lactiplantibacillus plantarum 6.2 in rats enhances bone and epithelial tissue repair by inhibiting NF-κB protein and promoting extracellular matrix synthesis via TGF-β - Rayne Taveira Rocha do Nascimento; Jannerson Cesar Xavier de Pontes; Rubens da Silva Araújo; Caio Henrique Alves Moreira; Ana Beatriz Rodrigues dos Santos; Rachel Passos Rezende; Carla Cristina Romano; Wallace Felipe Blohem Pessoa; Adriano Francisco Alves (Brazilian Journal of Microbiology, 2026)

Depositional processes on the outer shelf and upper slope of the Santos Bifurcation (SW Atlantic margin) - Michel Michaelovitch de Mahiques; Renata Hanae Nagai; César Barbedo Rocha; Paulo Alves de Lima Ferreira; Maria Carolina da Silva Nogueira de Matos; Raissa Basti Ramos; Maria Leticia de Melo Saraiva; Nicole de Magalhães Torquato; Rubens Cesar Lopes Figueira; Rodolfo Jasão Soares Dias; Mascimiliano de los Santos Maly; Luiz Antonio Pereira de Souza (Regional Studies in Marine Science, 2026)

Changes in sedimentary records induced by natural and anthropogenic influences: near the tip of Marambaia Barrier Island (Sepetiba Bay, southeastern Brazil) - Amanda Pacheco Seixas; Maria Virgínia Alves Martins; Heloisa Helena Gomes Coe; Karina Ferreira Chueng; Rubens Cesar Lopes Figueira; Paulo Alves de Lima Ferreira; Egberto Pereira; Denise Lara; Renata Cardia Rebouças; Miguel Tupinambá; Cleverson Guizan Silva; Murilo Barros Saibro; et al. (Journal of South American Earth Sciences, 2026)

Laboratory-based assessment of polycyclic aromatic hydrocarbon uptake in a Southwestern Atlantic endemic coral - Gislaine Vanessa de Lima; Marina Cunha Passarelli-Loura; Carolina Gonçalves de Lima; Gabriel Mendes Izar; Ana Cecília Rizzatti de Albergaria-Barbosa; Natália Menezes; Yasmim Caroline Anunciação Gomes; Luis Guilherme França Côrtes da Silva; Natanael Cícero Cavalcanti Bezerra; Cláudio Henrique Gomes Fialho; José Renato Mendes de Barros Correia; Gisele Olímpio da Rocha; et al. (Marine Pollution Bulletin, 2026)

Optimization of Moringa oleifera Lam. leaf hydrolysis for the release of bioactive di- and tripeptides with antioxidant and biostimulant potential - Fabiane Masala Rosário da Silveira; Grace Anne Vieira Magalhães-Ghiotto; Beatriz Santos Rocha; Evelin Lemos de Oliveira; Eduardo Cesar Meurer; Rosângela Bergamasco; Raquel Guttierres Gomes (Phytochemistry, 2026)

Disentangling natural and anthropogenic sedimentation: current and past pollution impact on Sepetiba Bay (southeastern Brazil) - Fabrício Leandro Damasceno; Maria Virgínia Alves Martins; Denise Lara Terroso; Miguel Angelo Mane; Caroline Adolphsson do Nascimento; Egberto Pereira; Rubens Cesar Lopes Figueira; João Graciano Mendonça Filho; Thaise M. Senez-Mello; Michael Martínez-Colón; Miguel Tupinamba; Renata Cardia Rebouças; et al. (Estuarine, Coastal and Shelf Science, 2026)

Thermohaline gradients and frontal regimes in the northwestern Tropical Atlantic - Dante C. Napolitano; Jonathan Gula; Solange Coadou-Chaventon; Sabrina Speich; Cesar B. Rocha; James C. McWilliams; Dongxiao Zhang; Xavier Carton (Ocean Science, 2026)
At the edge of the Amazon River plume, stirring by the North Brazil Current (NBC) and its eddies creates sharp surface thermohaline gradients on horizontal scales of 𝒪 (1–100) km. This study provides a comprehensive picture of these gradients and fronts associated with the region's distinctive dynamics. Saildrone observations show that the plume amplifies density gradient variability at all scales from 1–100 km, with frontal sharpness up to 75× stronger inside the plume than outside, with differences reaching 100× at scales below 3 km. Density gradients are partially reinforced or compensated by temperature-salinity variations, with net frontogenesis observed in both regions. To expand in-situ observations, we use a 1 km resolution CROCO (Coastal and Regional Ocean COmmunity model) simulation to assess the spatial distribution of surface fronts and their spatio-temporal variability. We characterize three distinct frontal regimes: (i) broken-up fronts parallel to shore occupy the plume core over the continental shelf, (ii) thin elongated fronts associated with NBC-plume interactions connect nearshore and offshore regions, and (iii) pools of anisotropic fronts driven by the seasonal mixed-layer cycle are present offshore. Salinity dominates density gradients throughout the year north of 15° N, whereas near-shore fronts exhibit seasonal shifts in temperature-salinity dominance linked to the Amazon discharge seasonality and NBC strength. Within the plume, freshwater filaments stirred by NBC rings systematically generate density-compensated fronts on their inner edge and reinforced fronts on their outer rim, a pattern with implications for energy cascades and tracer export.

Toxicity impacts of water treatment sludge disposal in rivers - Marcos Vinicius Mateus; Vinícius Carvalho Rocha; Mário Sérgio da Luz; Rhainer Guillermo Ferreira; Carla Eloísa Diniz dos Santos; Julio Cesar de Souza Inácio Gonçalves (Environmental Monitoring and Assessment, 2026)

Botulinum Toxin Type A for Refractory Postoperative Neuropathic Pain Following Cervicotomy: A Case Report - Cesar Sumita; Eduardo Rocha; Lucas Nishizawa (Toxicon, 2026)

Botulinum Toxin Type A for Refractory Neuropathic Pain After Cervicotomy and Thoracotomy: A Case Report - Eduardo Rocha; Cesar Sumita; Lucas Nishizawa (Toxicon, 2026)

Hydrodynamic control over shallow ferromanganese crust deposits in the West Rio Grande Rise - Pedro W.M. Souza-Neto; Muhammad Bin Hassan; João P.M. Amorim; Milton Borges-Silva; Cesar B. Rocha; Ilson C.A. da Silveira (Regional Studies in Marine Science, 2026)

Grain-size end-members and sortable silt of the terrigenous fraction associated with seafloor-current processes and depositional domains on the continental slope of the Santos basin (SW Atlantic margin) - Michel Michaelovitch de Mahiques; César Barbedo Rocha; Paulo Alves de Lima Ferreira; Samara Cazzoli y Goya; Lucas Santos Nunes; Rubens Cesar Lopes Figueira (Journal of Sedimentary Environments, 2026)

Sustainable discharge of lithium-ion batteries using coconut water: a natural alternative to chloride-based electrolytes - Helton Rogger Regatieri; Hugo Ferreira dos Santos; Ruan Vinícius Rocha Damaceno; Henrique Cesar Linhares Almeida; José Ricardo Cezar Salgado (Waste Management, 2026)

Vancomycin in neonatal patients: systematic review and call for standardized dosing and monitoring practices - Cesar Helbel; Camila Brusarosco Ferreira; Camila Ferreira Amaral Previato; Edvalkia Magna Teobaldo da Rocha; Guilherme Henrique Oliveira Silva; Diego Cardozo Mascarenhas; Gessilda de Alcântra Nogueira de Melo; Vagner Roberto Batistela; Estela Louro; Simone Tomás Gonçalves; Vanderly Janeiro; Roberto Kenji Nakamura Cuman (European Journal of Clinical Pharmacology, 2026)

High-resolution site characterization tools: application of fluorescence techniques to identify DNAPL in tropical lands - Lélia Cristina da Rocha Soares; Gabriela Paupitz Mendes; Alexandre Muselli Barbosa; Carlos Cesar Malta-Oliveira; Sandro Souto de Souto; Nestor Kenji Yoshikawa; Claudio Augusto Oller do Nascimento (Chemosphere, 2025)

Phosphatidylserine translocation, cholesterol spatial distribution, and acrosome reaction reliably distinguish sperm capacitation from cryoinjury in bovine sperm - Laura Nataly Garcia-Oliveros; Alexandre da Rocha Bozzi; Thais de Oliveira Cardoso Silva; Fernanda Baatsch Nascimento; Thainara Rodrigues de Oliveira; Ellen Lara Miguel; Maíra Bianchi Rodrigues Alves; Raissa Braido Rangel; André Furugen Cesar de Andrade; Rubens Paes de Arruda; Karl Kerns; Eneiva Carla Carvalho Celeghini (Cryobiology, 2025)

The Andrelândia Group as a record of a Neoproterozoic/Mesoproterozoic platform basin in the São Francisco craton (SE Brazil): U–Pb and Lu–Hf results and tectonic implications - Rafael Cardoso de Moraes Telles; Rodrigo Peternel Machado Nunes; Ariane Felix Coelho Azevedo; Pedro Costa Furtado; Marcos Vinicius Ferreira Fontainha; André Campos Rocha Pinto; Felippe Amaral; Armando Dias Tavares; Mauro Cesar Geraldes (Journal of Sedimentary Environments, 2025)

Rheological Properties and Process Temperature Prediction for the Hot Melt Extrusion of Artesunate with Soluplus®/Span®20 - Fabio Moyses Lins Dantas; Maria Helena Miguez da Rocha-Leão; Daniel Lins de Sales; André Luís Marcomini; Cesar Augusto Gonçalves Beatrice; Carlos Henrique Scuracchio; Pedro Henrique da Rocha Franco; Alessandra Lifsitch Viçosa (AAPS PharmSciTech, 2025)

Anthropogenic pollutants in the Southwestern Atlantic Ocean slope: Is the Santos Bifurcation region a potential sink for organic contaminants? - Felipe R. Santos; Márcia C. Bícego; Lígia D. Araújo; Rafael A. Lourenço; Satie Taniguchi; César C. Martins; Rubens C.L. Figueira; Ilana K.C. Wainer; Cesar B. Rocha; Michel M. Mahiques (Marine Pollution Bulletin, 2025)

Stabilization of Dispersive Soil Using Calcium Lignosulfonate: Strength, Durability, and Microstructure Assessment - Lisandra Rocha de Moraes; Nilo Cesar Consoli; Cezar Augusto Burkert Bastos (Geotechnical and Geological Engineering, 2025)

Impact caused by the transportation of iron ore on the beaches of a tourist region in SE Brazil: Mangaratiba (Rio de Janeiro) - Sheila R. Arruda; Maria Virgínia Alves Martins; Graziele Arantes Reis; Denise Lara Terroso; Rafael Cardoso de Moraes Telles; Diego Soares Lopes Lima; Mauro Cesar Geraldes; Francisco Dourado; Murilo Barros Saibro; André Luiz Carvalho da Silva; Fabrício Leandro Damasceno; Renata Cardia Rebouças; et al. (Journal of Sedimentary Environments, 2025)
The municipality of Mangaratiba, located in the Sepetiba Bay region (Rio de Janeiro State; Southeast Brazil), has been taken over for several years by large structures, including real estate, tourism, industrial and ore export activities. Transportation and port activities, especially iron ore logistics from the Iron Quadrangle region (MG), have changed the landscape, particularly the beaches in the municipality of Mangaratiba. Thus, this study applies a multiproxy approach (textural, mineralogical, elemental and lead isotopic data) to iron ore samples and ore particles found on beaches and a waterfall from the Mangaratiba region, aiming to identify the impact caused by ore transport and dispersion in the study area. The results show that the sands of Sahy, Ribeira, Santo Antônio, Muriqui, Mangatiba’s Centro, Junqueira, Saco and Itacuruçá beaches have relatively high contents of pyrite, hematite, magnetite/maghemite and goethite, which are part of the ore composition samples. The variation in the 206 Pb/ 204 Pb and 207 Pb/ 204 Pb values show similarity in the isotopic fingerprints in the Fe ore samples and ore particles found on beaches, suggesting common sources. Iron ore has the highest sum of toxic units (ΣTUs 17.9–21.8). The highest toxicity degree ratio (TDR) based on ΣTUs values was found in the ore samples and at Junqueira Beach, Saco Beach, near the train line, and Santo Antônio Beach, close to the Guaiba Island iron ore export terminal. This work shows that ore dispersion during transportation is causing environmental degradation on most Mangaratiba beaches. There is a risk of exposure to the ore particles by the people who visit the beaches and inhabit the region and the organisms that live there. People may inhale dust (enriched in Sb, Mn, Fe, Cd, Ag, and Ge), which is dispersed during the ore transportation by strong wind and displays irritation of the skin and eyes, among other diseases. This study indicates the need to adopt mitigating measures to avoid severe environmental damage and public health problems.

3D modeling and fluid flow simulations along fault zone affected by silicification in Rio do Peixe Basin, Brazil - Renan Nicolau Ribeiro da Rocha; Francisco Cézar Costa Nogueira; Cayo Cesar Cortez Pontes; Thiago Pedro de Lira Gomes; David Lino Vasconcelos; Leonardo Carvalho Palhano; Jorge Andre Braz de Souza; Yoe Alain Reyes Perez; Matheus Amador Nicchio (Journal of South American Earth Sciences, 2025)

A decision-making flowchart for tailings Stabilization: Assessing environmental and economic impacts - Rodrigo Beck Saldanha; Andres Lotero; Fernanda Jaskulski; Nilo Cesar Consoli; Cecília Gravina da Rocha (Journal of Cleaner Production, 2025)

A novel zooplankton-based environmental monitoring tool for coastal impacted areas: The case of the Doce River dam rupture - Gustavo Martins Rocha; Bianca Salvador; Gabriel Harley Costa Santos; Laura Rodrigues da Conceição; Priscila Teixeira-Amaral; Maikon Di Domenico; Diego de Arruda Xavier; Eduardo Schettini Costa; Renata Caiado Cagnin; Cesar Alexandro da Silva; Mayara Bandeira; Mônica de Souza Mendes; et al. (Estuarine, Coastal and Shelf Science, 2025)

Contamination by Potentially Toxic Elements (PTEs) in Agricultural Products Grown Around Sepetiba Bay, Rio de Janeiro State (SE Brazil) - Graziele Arantes Reis; Maria Virginia Alves Martins; Lisia Maria Gobbo Santos; Santos Alves Vicentine Neto; Fernando Barbosa Junior; Mauro Cesar Geraldes; Sérgio Bergamaschi; Rubens Cesar Lopes Figueira; Carla Patinha; Eduardo Ferreira da Silva; Fernando Rocha (Archives of Environmental Contamination and Toxicology, 2025)
The contamination of soil, water, and air by potentially toxic elements (PTEs) allows the transfer of metals to food. When introduced into food through soil, PTEs are absorbed by plant roots and transported to the bloodstream. The region surrounding Sepetiba Bay (SB), a densely populated area intensively exploited for tourist purposes, is one of the most contaminated by PTEs in the southeastern region of Brazil. Therefore, this study aims to evaluate (by ICP-MS) the concentrations of PTEs in agricultural products (roots, fruits, leaves, seeds, cheese, and eggs) cultivated and sold by rural producers in the region surrounding SB. The 26 food types selected for this study were produced in this region and purchased at local markets. The results for the analyzed foods revealed relatively high concentrations of Zn > Cu > Ni > Cr > As > Pb > Co > Hg > Cd, exceeding the limits established by ANVISA and international laws. Cluster analysis (CA) and principal component analysis (PCA) grouped the PTEs according to their possible sources: ore transport (Zn, Cu, Pb, and Cd), natural (Hg, Cr, and Ni), and fertilizers (Co and As). The CA allowed us to distinguish two main food groups in terms of the enrichment of PTEs. Group 1 contains leaves, animal products, and seeds with higher levels of Hg, Cr, Ni, Co, and As. Group 2 includes roots and fruits, which have higher concentrations of Zn, Cu, Pb, and Cd than Group 1. The Hazard Quotient (HQ) suggests that As and Cr pose a higher risk in foods of CA-Group 1 (leaves, animal products, and seeds). Hazard Index (HI) values > 1 indicate a risk of probable long-term carcinogenesis in adults. Thus, this study reveals that the continued consumption of food produced in the region surrounding SB could cause health problems for the local population.

Changes in the sedimentation and oxygen depletion during the Heinrich stadials 4 and 5 in a distal region of the NW Iberian Margin - Layla Cristine da Silva; Maria Virgínia Alves Martins; Daniel Rey García; Ana Bernabeu Tello; Paula Álvarez Iglesias; Denise Lara Terroso; Belén Rubio Armesto; Murilo Barros Saibro; Silvia Helena de Melo Sousa; Sérgio Bergamaschi; Egberto Pereira; Rodolfo Dino; et al. (Quaternary International, 2025)

Disentangling wavy and vortical motions in concurrent snapshots of the sea surface height and velocity - Chuanyin Wang; Zhiyu Liu; Hongyang Lin; Cesar Rocha; Qinghua Yang; Dake Chen; Junbin Gong (Ocean Modelling, 2025)

Effects of water deficit stress and salicylic acid preharvest treatments on postharvest biochemical parameters of potato - Andres Felipe Gaona Acevedo; Vander Rocha Lacerda; Alberto Mario Arroyo Avilez; Julio Cesar de Almeida Silva; Rogerio Lopes Vieites (Food and Humanity, 2025)

Provenance evolution and sedimentary records in a rift basin: U-Pb Detrital zircon and petrography of sandstones of the Volta Redonda Basin (central segment of the Continental Rift of Southeastern Brazil) - Carlos Eduardo Sales de Oliveira; Luiz Carlos Bertolino; Mauro Cesar Geraldes; Renato Rodriguez Cabral Ramos; André Pires Negrão; André Campos Rocha Pinto (Journal of South American Earth Sciences, 2025)

Comparative histology and histochemistry of the parotid and sublingual glands in the white-eared opossum (Didelphis albiventris) - Aline Herrera Farha; Tais Harumi de Castro Sasahara; Silvio Pires Gomes; Leandro Luís Martins; Letícia Rocha Inamassu; Bruno Cesar Schimming (Zoomorphology, 2025)

A global soil spectral grid based on space sensing - José A.M. Demattê; Rodnei Rizzo; Nícolas Augusto Rosin; Raul Roberto Poppiel; Jean Jesus Macedo Novais; Merilyn Taynara Accorsi Amorim; Heidy Soledad Rodriguez-Albarracín; Jorge Tadeu Fim Rosas; Bruno dos Anjos Bartsch; Letícia Guadagnin Vogel; Budiman Minasny; Sabine Grunwald; et al. (Science of The Total Environment, 2025)

Assessing the behavior of food handlers wearing face masks and the passage of bacteria through disposable masks - Cris Rocha Pinto Magalhães; Nathanyelle Soraya Martins de Aquino; Julia de Moraes Vieira; Claudia Titze Hessel Gonçalves; Eduardo Cesar Tondo (Brazilian Journal of Microbiology, 2025)

Cryogenian magmatic arc detrital ages and superposition of metamorphic events in metasedimentary rocks from the Andrelândia and Juiz de Fora domains, Juiz de Fora, Minas Gerais - André Campos Rocha; Beatriz Paschoal Duarte; Mauro Cesar Geraldes; Ariane Felix Coelho Azevedo; Thayla Almeida Teixeira Vieira; Rafael Cardoso de Moraes Telles; Marcos Silva Machado; Wagner Travassos Lemos; Julio Cezar Mendes (Journal of South American Earth Sciences, 2025)

Multiplatform Path-ComDim study of Capixaba, indigenous and non-indigenous Amazonian Canephora coffees - Michel Rocha Baqueta; Douglas N. Rutledge; Enrique Anastácio Alves; Manuela Mandrone; Ferruccio Poli; Aline Coqueiro; Augusto Cesar Costa-Santos; Ana Paula Rebellato; Gisele Marcondes Luz; Bruno Henrique Fermino Goulart; Eduardo Jorge Pilau; Juliana Azevedo Lima Pallone; et al. (Food Chemistry, 2025)

Thinning Strategies to Optimize Genetic Gain and Population Size in Eucalyptus pellita Breeding - Paulo Henrique Müller da Silva; Guilherme Nichele da Rocha; Marcio Araujo; Andrei Caíque Pires Nunes; Rinaldo Cesar de Paula (Tree Genetics & Genomes, 2024)

Identifying putative allergens from Cenostigma pluviosum pollen using proteomic bioinformatics - Jaime Olbrich Neto; Bruna Cavecci-Mendonça; Sandra Regina Leite Rosa Olbrich; Francielle Ramalho Rocha; Eloisa Fornaro Clemente; Bruno Cesar Rossini; Lucilene Delazari dos Santos (Molecular Biology Reports, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Monitoring invasive exotic grass species in ecological restoration areas of the Brazilian savanna using UAV images - Marcos Vinicius Rezende de Ataíde; Silvia Barbosa Rodrigues; Tamilis Rocha Silva; Augusto Cesar Silva Coelho; Ana Wiederhecker; Daniel Luis Mascia Vieira (Remote Sensing Applications: Society and Environment, 2024)

Comparison of α and β-acid isomerization in hops and beer using HPLC, confocal microscopy, spectrofluorimetry and chemical analysis of metabolites and essential oils in flowers of different hop cultivars produced in Brazil - Francisco Mateus Gomes do Nascimento; Maria Teresa Salles Trevisan; Manoel Lourenço Alves Neto; Robert Wyn Owen; Edy Sousa de Brito; Lorena Mara Alexandre e Silva; Késya Amanda Dantas Rocha; Carlos Lenz Cesar; Hernandes Faustino de Carvalho; Vitor Bianchin Pelegati; Sthefanny Alves da Silva; Samuel Pedro Dantas Marques (Food Chemistry, 2024)

Geotech social impacts: Development, application, and comparative analysis - Suéllen Tonatto Ferrazzo; Mariana Tonini de Araújo; Nilo Cesar Consoli; Cecília Gravina da Rocha (Environmental Impact Assessment Review, 2024)

The Rio Grande Rise circulation: Dynamics of an internal tide conversion hotspot in the Southwestern Atlantic - Pedro W.M. Souza-Neto; Ilson C.A. da Silveira; Cesar B. Rocha; Cauê Z. Lazaneo; Paulo H.R. Calil (Progress in Oceanography, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Unveiling the impact of antimicrobial-infused water on hydroponic baby leafy vegetables (lettuce, rocket, and watercress): Physiological effects and food safety - Daiane Cristina Rocha; Leticia Yoshie Kochi; Rafael Shinji Akiyama Kitamura; Julio Cesar Moreira Brito; Keite da Silva Nogueira; Marcelo Pedrosa Gomes (Journal of Environmental Chemical Engineering, 2024)

Environmental, economic, and social impacts of sugar cane bagasse and eggshell wastes for soil stabilization - Mariana Tonini de Araújo; Suéllen Tonatto Ferrazzo; Nilo Cesar Consoli; Cecília Gravina da Rocha (Environmental Science and Pollution Research, 2024)

Sand subfractions by proximal and satellite sensing: Optimizing agricultural expansion in tropical sandy soils - Luis Augusto Di Loreto Di Raimo; Eduardo G. Couto; Raul R. Poppiel; Danilo Cesar de Mello; Ricardo S.S. Amorim; Gilmar Nunes Torres; Edwaldo D. Bocuti; Gustavo Vieira Veloso; Elpídio Inácio Fernandes-Filho; Márcio Rocha Francelino; José A.M. Demattê (CATENA, 2024)

Temporal dynamics of benthic communities in a hypereutrophic bay through functional groups and abiotic variables - Amanda Cunha de Souza Coração; Erick Alves Pereira Lopes-Filho; Rodolfo Pinheiro da Rocha Paranhos; Paulo Cesar Paiva; Joel Campos De Paula (Marine Pollution Bulletin, 2023)

Effect of nanomaterials on the bioavailability of metals in sediments from a highly impacted tropical coastal environment - Michele Maria da Silva; Maria Angélica Vergara Wasserman; Júlio Cesar de Faria Alvim Wasserman; Daniel Vidal Pérez; Tatiane Rocha Pereira; Manuella Borges Barreto; Ralph Santos-Oliveira (Environmental Nanotechnology, Monitoring & Management, 2023)

Constraining the duration of the southern Gondwana Irati-Whitehill Sea through cyclostratigraphy and its relation with deep-time astronomical solutions - Aurélio F. Silva; Thiago P. Santos; Pedro L.A. Xavier; Norberto Dani; Cesar L. Schultz; Marcus V.D. Remus; Ruy P. Philipp; Raysa M. Rocha; Daniel R. Franco; Marco António L. da Silva (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Responses of broilers challenged by Eimeria maxima fed with different levels of dietary balanced protein - Luís Filipe Villas Boas de Freitas; Juliano Cesar de Paula Dorigam; Matheus de Paula Reis; Bernardo Rocha Franco Nogueira; Rony Riveiros Lizana; Nilva Kazue Sakomura (Research in Veterinary Science, 2023)

Pharmaceutical-contaminated irrigation water: implications for ornamental plant production and phytoremediation using enrofloxacin-accumulating species - Camila Silva Rocha; Leticia Yoshie Kochi; Júlio Cesar Moreira Brito; Rafael Shinji Akiyama Kitamura; Daniella Moreira Carneiro; Michele Valquíria dos Reis; Marcelo Pedrosa Gomes (Environmental Science and Pollution Research, 2023)

Genome-wide assessment of genetic diversity in Mexican Sardo Negro breed - Ricardo Martínez-Rocha; Antonio Reyes-Ceron; Joel Domínguez-Viveros; Jorge Hidalgo; Rafael Núñez-Domínguez; Rodolfo Ramírez-Valverde; Neon Larios-Sarabia; Cesar Villegas-Gutiérrez (Livestock Science, 2023)

Lessons from the invasion front: Integration of research and management of the lionfish invasion in Brazil - Marcelo O. Soares; Pedro H.C. Pereira; Caroline V. Feitosa; Rodrigo Maggioni; Rafael S. Rocha; Luis Ernesto Arruda Bezerra; Oscar S. Duarte; Sandra V. Paiva; Eurico Noleto-Filho; Maiara Queiroz M. Silva; Mayra Csapo-Thomaz; Tatiane M. Garcia; et al. (Journal of Environmental Management, 2023)

Dynamic Properties of Reclaimed Asphalt Pavement–Green Cement Blends for Road Base Layer - Nilo Cesar Consoli; Aziz Tebechrani Neto; Aghileh Khajeh; Mahdi Salimi; Luciano Pivoto Specht; Pablo Menezes Vestena; Cecília Gravina da Rocha (Geotechnical and Geological Engineering, 2023)

The science we need for the beaches we want: frontiers of the flourishing Brazilian ecological sandy beach research - Guilherme Nascimento Corte; Yasmina Shah Esmaeili; Tatiana Fabricio Maria; Leonardo Lopes Costa; Gustavo Mattos; Helio Herminio Checon; Nicole Malinconico; Paulo Cesar Paiva; Paula Debiasi; Tatiana Cabrini; Victor Corrêa Seixas; Eduardo Bulhões; et al. (Frontiers in Marine Science, 2023)

Nicotinic acid addition to equine frozen semen extender influences the number of sperm bound to bovine oviduct explants - Natália de Castro Alves; Aléxia Vitória Rocha Dutra; Marina Morra Freitas; Jade Raquel Dias Farias; Camilla Silva dos Anjos; Fernando Antônio de Souza; Ângela Maria Quintão Lana; Cesar Lopes Horta; Isis Luise Pires de Oliveira; Monique de Albuquerque Lagares (Journal of Equine Veterinary Science, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Bivariate GWAS reveals pleiotropic regions among feed efficiency and beef quality-related traits in Nelore cattle - Carlos Eduardo Buss; Juliana Afonso; Priscila S. N. de Oliveira; Juliana Petrini; Polyana Cristine Tizioto; Aline S. M. Cesar; Emanuele Cristina Gustani-Buss; Tainã Figueiredo Cardoso; Gregori A. Rovadoski; Wellison Jarles da Silva Diniz; Andressa Oliveira de Lima; Marina Ibelli Pereira Rocha; et al. (Mammalian Genome, 2023)

Development of Recirculating Photocatalytic Reactor with TiO2 Supported on Post-consumption Polystyrene Film: Evaluation of Hazardous Food Colorants Degradation - Maressa Maria de Melo Santos Moura; Graziele Elisandra do Nascimento; Deivson Cesar Silva Sales; Joan Manuel Rodríguez-Díaz; Otidene Rossiter Sá da Rocha; Marta Maria Menezes Bezerra Duarte (Water, Air, & Soil Pollution, 2022)

Control of oceanic circulation on sediment distribution in the southwestern Atlantic margin (23 to 55° S) - Michel Michaelovitch de Mahiques; Roberto Violante; Paula Franco-Fraguas; Leticia Burone; Cesar Barbedo Rocha; Leonardo Ortega; Rosangela Felicio dos Santos; Bianca Sung Mi Kim; Rubens Cesar Lopes Figueira; Marcia Caruso Bícego (Ocean Science, 2021)
In this study, we interpret the role played by ocean circulation in sediment distribution on the southwestern Atlantic margin using radiogenic Nd and Pb isotopes. The latitudinal trends for Pb and Nd isotopes reflect the different current systems acting on the margin. The utilization of the sediment fingerprinting method allowed us to associate the isotopic signatures with the main oceanographic features in the area. We recognized differences between Nd and Pb sources to the Argentinean shelf (carried by the flow of Subantarctic Shelf Water) and slopes (transported by deeper flows). Sediments from Antarctica extend up to the Uruguayan margin, carried by the Upper and Lower Circumpolar Deep Water. Our data confirm that, for shelf and intermediate areas (the upper 1200 m), the transfer of sediments from the Argentinean margin to the north of 35∘ S is limited by the Subtropical Shelf Front and the basin-wide recirculated Antarctic Intermediate Water. On the southern Brazilian inner and middle shelf, it is possible to recognize the northward influence of the Río de la Plata sediments carried by the Plata Plume Water. Another flow responsible for sediment transport and deposition on the outer shelf and slope is the southward flow of the Brazil Current. Finally, we propose that the Brazil–Malvinas Confluence and the Santos Bifurcation act as boundaries of geochemical provinces in the area. A conceptual model of sediment sources and transport is provided for the southwestern Atlantic margin.

The P-y Response of Laterally Loaded Flexible Piles in Residual Soil - Nilo Cesar Consoli; Naiara da Costa Reginato; Luizmar da Silva Lopes Júnior; Marcelo Maia Rocha; Vítor Pereira Faro; Ricardo Bergan Born (Geotechnical and Geological Engineering, 2021)

Disentangling natural vs. anthropogenic induced environmental variability during the Holocene: Marambaia Cove, SW sector of the Sepetiba Bay (SE Brazil) - Wellen Fernanda Louzada Castelo; Maria Virgínia Alves Martins; Michael Martínez-Colón; Josefa Varela Guerra; Tatiana Pinheiro Dadalto; Denise Terroso; Maryane Filgueiras Soares; Fabrizio Frontalini; Wânia Duleba; Orangel Antonio Aguilera Socorro; Mauro Cesar Geraldes; Fernando Rocha; et al. (Environmental Science and Pollution Research, 2021)

Can the Intermediate Western Boundary Current recirculation trigger the Vitória Eddy formation? - Dante C. Napolitano; Cesar B. Rocha; Ilson C. A. da Silveira; Iury T. Simoes-Sousa; Glenn R. Flierl (Ocean Dynamics, 2021)

Auramine dyes induce toxic effects to aquatic organisms from different trophic levels: an application of predicted non-effect concentration (PNEC) - Carina Cristina de Jesus Azevedo; Rhaul de Oliveira; Paula Suares-Rocha; Diego Sousa-Moura; Augusto Tianwen Li; Cesar Koppe Grisolia; Gisela de Aragão Umbuzeiro; Cassiana Carolina Montagner (Environmental Science and Pollution Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Suspension training vs. traditional resistance training: effects on muscle mass, strength and functional performance in older adults - Samuel Domingos Soligon; Deivid Gomes da Silva; João Guilherme Almeida Bergamasco; Vitor Angleri; Ricardo Alessandro Medalha Júnior; Nathalia Fernanda Dias; Sanmy Rocha Nóbrega; Marcelo de Castro Cesar; Cleiton Augusto Libardi (European Journal of Applied Physiology, 2020)

Latitudinal patterns of species diversity on South American rocky shores: Local processes lead to contrasting trends in regional and local species diversity - Juan J. Cruz‐Motta; Patricia Miloslavich; Edlin Guerra‐Castro; Alejandra Hernández‐Agreda; Cesar Herrera; Francisco Barros; Sergio A. Navarrete; Roger D. Sepúlveda; Tim M. Glasby; Gregorio Bigatti; Maritza Cardenas‐Calle; Pedro B. M. Carneiro; et al. (Journal of Biogeography, 2020)
Aim We evaluated whether patterns of species diversity (α, β and γ) of rocky shore assemblages followed latitudinal gradients (i.e. LDGs) along the South American coasts, and tested hypotheses related to potential processes sustaining or disrupting the expected LDG pattern at various spatial scales. Location Coasts of South America. Taxon Macroalgae and sessile/slow‐moving macrofauna on intertidal rocky shores. Methods We evaluated changes in species composition across 143 sites. The degree of replacement and loss of species at different spatial scales (i.e. coasts, regions and sites) were estimated to help distinguish among ecological, historical and evolutionary hypotheses for explaining LDGs. Furthermore, components of diversity and taxonomic distinctness were measured, and variability in these measures was decomposed using analysis of covariance. Finally, we examined relationships between diversity and a suite of environmental and anthropogenic variables to identify potential mechanisms that may be responsible for the reported spatial relationships. Results Species composition varied with latitude, and this variability was relatively consistent on both coasts. At all spatial scales, replacement of species was the dominant phenomenon (>95%), rather than loss in the total number of species ( Main conclusions Species diversity of South American rocky shores followed, with interruptions, LDGs. The trend of those LDGs, however, depended on the scale and metric used to describe diversity. It is proposed that patterns of LDGs at various scales are not the result of a single overarching process but are strongly influenced by local and regional processes. Although the most evident environmental gradient was the decrease in SST towards the south, it was demonstrated that regional and local environmental variables were also important for understanding the increase in regional β‐diversity towards the tropics.

Characterization of mating type and the diversity of pathotypes of Phytophthora infestans isolates from Southern Brazil - Victor Hugo Casa-Coila; Cesar Bauer Gomes; Israel Lima-Medina; Dediel Junior A. Rocha; Ailton Reis (Journal of Plant Diseases and Protection, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Degradation of Textile Dyes Employing Advanced Oxidative Processes: Kinetic, Equilibrium Modeling, and Toxicity Study of Seeds and Bacteria - Rayany Magali da Rocha Santana; Lívia Carlini Vieira Charamba; Graziele Elisandra do Nascimento; Julierme Gomes Correia de Oliveira; Deivson Cesar Silva Sales; Marta Maria Menezes Bezerra Duarte; Daniella Carla Napoleão (Water, Air, & Soil Pollution, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Multi-hydro hydrological modelling of a complex peri-urban catchment with storage basins comparing C-band and X-band radar rainfall data - Bianca Alves de Souza; Igor da Silva Rocha Paz; Abdellah Ichiba; Bernard Willinger; Auguste Gires; Jose Carlos Cesar Amorim; Marcelo de Miranda Reis; Bruno Tisserand; Ioulia Tchiguirinskaia; Daniel Schertzer (Hydrological Sciences Journal, 2018)

Development of an environmental management overview in the Farol de São Tomé Plain - Brazil - Julio Cesar Wasserman; Jacob Binsztok; Ana Regina da Rocha Araújo; Débora Chueiri (Journal of Coastal Conservation, 2018)

Diphenyl diselenide modulates nucleotidases, reducing inflammatory responses in the liver of Toxoplasma gondii-infected mice - Pedro H. Doleski; Daniela B. R. Leal; Vanessa S. Machado; Nathieli B. Bottari; Alessandra G. Manzoni; Emerson A. Casali; Cesar E. J. Moritz; Ana C. A. Rocha; Giovana Camillo; Fernanda F. Vogel; Lenita M. Stefani; Ricardo E. Mendes; et al. (Purinergic Signalling, 2017)

Assessment of DDT and Metabolites in Soil and Sediment of Potentially Contaminated Areas of Belém, Amazon Region, Brazil - Andreia Oliveira Rodrigues; Larissa Costa de Souza; Cássia Christina da Silva Rocha; Amilton Cesar Gomes da Costa; Rosivaldo de Alcântara Mendes (Bulletin of Environmental Contamination and Toxicology, 2017)

Water quality of a coastal lagoon (ES, Brazil): abiotic aspects, cytogenetic damage, and phytoplankton dynamics - Ian Drumond Duarte; Nayara Heloisa Vieira Fraga Silva; Iara da Costa Souza; Larissa Bassani de Oliveira; Lívia Dorsch Rocha; Mariana Morozesk; Marina Marques Bonomo; Thaís de Almeida Pereira; Mauro Cesar Dias; Valéria de Oliveira Fernandes; Silvia Tamie Matsumoto (Environmental Science and Pollution Research, 2017)

Fertigated Sugarcane Yield and Carbon Isotope Discrimination (Δ13C) Related to Nitrogen Nutrition - Oriel Tiago Kölln; Glauber José de Castro Gava; Heitor Cantarella; Henrique Coutinho Junqueira Franco; Raul Andres Martinez Uribe; Luiz Eduardo da Rocha Pannuti; Paulo Cesar Ocheuze Trivelin (Sugar Tech, 2016)

Application of Fenton, photo-Fenton, solar photo-Fenton, and UV/H2O2 to degradation of the antineoplastic agent mitoxantrone and toxicological evaluation - Rodrigo Pereira Cavalcante; Lucas da Rocha Sandim; Danielle Bogo; Antônio Marcos Jacques Barbosa; Marly Eiko Osugi; Matildes Blanco; Silvio Cesar de Oliveira; Maria de Fatima Cepa Matos; Amilcar Machulek; Valdir Souza Ferreira (Environmental Science and Pollution Research, 2013)